Enhancing Village Self-Reliance: Campground Development and MSME Support in Girikerto Village, Sleman - Muhammad Hamdi; Gumelar, Bagus (Universitas Veteran Bangun Nusantara, 2025)
This community service project focuses on enhancing economic independence in Girikerto Village, Sleman, through the development of Merapi Valley Campground and supporting local Micro, Small, and Medium Enterprises (MSMEs), specifically a goat milk soap business. The project implemented a comprehensive approach aligning with Sustainable Development Goals (SDGs) 3, 8, 9, 11, 13, and 15. Methods included stakeholder socialization, BPOM certification assistance, outbound package creation, website development, and infrastructure enhancement. The program successfully established tourism packages, created an outbound arena, developed digital marketing platforms, and initiated the BPOM certification process for the MSME product. While economic targets have not yet been fully realized, continued assistance and integration with university service-learning programs are recommended to ensure sustainability. This case demonstrates how university-community partnerships can effectively strengthen rural economies through tourism development and MSME support. Keywords: Rural Development, Tourism, MSMEs, Sustainable Development, Community Empowerment